Mixing Analysis of Bamboo and Natural Iron Sand as a Magnetic Material - Sihombing, Helena Artasari; Riana, Martha; Humaidi, Syahrul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine the magnetic properties of Fe3O4 synthesized from rope bamboo and natural iron sand. In this study, natural magnetic bio-char of bamboo and iron sand was synthesized by the co-precipitation method at a calcination temperature of 500oC. Then it was characterized through several tests, namely XRD and VSM. The results of the XRD test showed that the synthesis of natural bamboo + iron sand produced HKL peaks that were identical to Fe3O4 where these peaks were the peaks of magnetite and hematite. Magnetic properties were tested using VSM through a hysteresis curve with samples classified as soft magnets.